Induced sputum genes associated with spirometric and radiological disease severity in COPD ex-smokers. Issue 6 (24th March 2011) - Singh, Dave; Fox, Steven M; Tal-Singer, Ruth; Plumb, Jonathan; Bates, Stewart; Broad, Peter; Riley, John H; Celli, Bartolome
Abstract : Background: Induced sputum is used to sample inflammatory cells, predominantly neutrophils and macrophages, from the airways of COPD patients. The author's aim was to identify candidate genes associated with the degree of airflow obstruction and the extent of emphysema by expression profiling, and then to confirm these findings for selected candidates using PCR and protein analysis. Methods: Two sputum studies were performed in Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 2–4 COPD ex-smokers from the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) cohort. First, gene array profiling at baseline in samples from 148 patients. The findings were replicated in a separate population of 176 patients using real-time PCR. The findings for one selected gene IL-18R were further analysed using immunohistochemistry in lung tissue and induced sputum from patients outside the ECLIPSE cohort. Results: Gene expression profiling revealed changes in 277 genes associated with GOLD stage 2 versus 3 and 4, and 198 genes with changes associated with the degree of emphysema (p<0.01 for each gene). Twelve of these candidate genes were analysed by PCR in the replication cohort, with significant changes (p<0.05) observed for 11 genes. IL-18R protein expression was higher on alveolar macrophages in lung tissue of COPD patients (mean 23.2%) compared to controls (mean ex-smokers 2% and non-smokers 2.5%). Conclusion: Gene expression profiling in sputum cells identified candidate genes that may play roles in molecular mechanisms associated with COPD. The replication by PCR and protein in different studies confirms these findings, and highlights a potential role for IL-18R upregulation in severe COPD.